Modeling of a liquid desiccant dehumidification system for close type greenhouse cultivation. (1st January 2017) - Ali, Ameer; Ishaque, Kashif; Lashin, Aref; Al Arifi, Nassir
Abstract: Solar energy, heat exchange with the ambient & plants and vapor balance are the key variables for modeling the greenhouse. However, due to solar energy, crops continuously produce water vapors through evapotranspiration, which continuously need to be dehumidified to maintain the relative humidity in the required range. Therefore, modeling and simulation of dehumidification system seems to be indispensable, as it will help to investigate the workability and operating performance of the greenhouse. Hence, this work models and simulates the various components of liquid desiccant based dehumidification system for greenhouse cultivation. Each component of an entire stand-alone dehumidification system, namely reference greenhouse, dehumidification & regeneration reactors and solar collector are thoroughly modeled in MATLAB Simulink environment. The overall system can be effectively utilized to analyze the working performance for greenhouse cultivation. The obtained results indicate that proposed modeling is effective in showing the moisture removal, which crops generate inside the greenhouse. Besides, the developed system is very unique, as most of the previous desiccant system are designed for domestic and commercial buildings. It is envisaged that this work is very useful for the researchers and energy professionals to develop efficient integrated systems for stand-alone buildings. Graphical abstract: Moisture contents in air and liquid desiccant along the packed bed. Highlights: Modeling and simulation of liquid desiccant based greenhouse dehumidification system. Dehumidification system assists to analyze the working performance for greenhouse cultivation. Model is capable of removing the moisture, which is generated by crops. Proposed modelling requires lower value of heat for regeneration.